Financial Performance of Infrastructure Companies Before and During the Covid-19 - Wina Nofrima Fitri; Wiwik Andriani; Rangga Putra Ananto (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
This research looks at what was carried out to decide the difference in the financial performance of infrastructure companies listed on the Indonesian Stock Exchange before and during COVID-19. This observation uses a quantitative approach to comparative studies. Sampling for this study was performed using a targeted sampling technique, resulting in a sample of 31 infrastructure companies. This research used secondary data from annual reports provided by the IDX website. Data were processed using SPSS software version 25, and hypothesis tests were performed using the standard Kolmogorov-Smirnov test and Wilcoxon signed rank test. The study measures financial performance by eight criteria: current ratio, short-term ratio, total debt, leverage, total asset turnover, and asset turnover ratio. , net profit margin, and investment rate of return. Complete As a result, and we found a significant difference before and after Covid-19 in current ratios, short-term ratios, total debt, total asset turnover ratio, net profit margin, and rate of return on investment. Furthermore, there were no significant differences in indebtedness and debt turnover before and during Covid-19.